Brief Report: Frailty in Aging People Living With HIV. (1st November 2021) - Lellouche, Lionel; Gutierrez, Laure-Anne; Leclercq, Pascale; Zaegel-Faucher, Olivia; Bernard, Louis; Vassallo, Matteo; Barbuat, Claudine; Ozguler, Anna; Zins, Marie; Nailler, Laura; Reynes, Jacques; Berr, Claudine; et al.
Abstract : Background: We compared the prevalence of frailty among aging people living with HIV (PLHIV) with people without HIV from the ANS EP58 HAND 55–70 Study. Methods: Cross-sectional multicentric study which consecutively included 200 PLHIV and 1000 people without HIV from the French national CONSTANCES cohort, matched on age, sex, and education level. PLHIV were aged 55–70 years, with a HIV viral load < 50 copies/mL and a lymphocyte T-CD4 level > 200 cells/µL for the last 24 and 12 months, respectively. We measured frailty (>2 items) and prefrailty (one or 2 items) using a proxy of the 5-item Fried score. Multivariate logistic regression was performed to assess the association between HIV and frailty/prefrailty, adjusting for demographic, social, behavioral, and comorbidity confounders. Results: Outcome measures were available for 192 PLHIV and 822 people without HIV. The median age was 62 years, and 84.9% were men. Among PLHIV, the median CD4 cell count was 645.5 cells/µL. Prevalence of frailty/prefrailty was 5.73%/57.3% in PLHIV vs. 1.73%/52.2% in people without HIV, respectively. HIV was associated with prefrailty/frailty [odds ratio = 1.89; 95% confidence interval = 1.37 to 2.61), but after adjusting for social and behavioral factors and comorbidities, HIV was not significantly associated with prefrailty/frailty (odds ratio = 1.24; 95% confidence interval: = 0.84 to 1.81). In PLHIV only, frailty/prefrailty was associated with depressive symptomatology, kidney disease, and time since HIV infection. Conclusions: Prevalence of frailty is increased in aging PLHIV with well-controlled HIV disease, but other factors than HIV are predominant, particularly depression and comorbidities. Abstract : Supplemental Digital Content is Available in the Text.